2020
DOI: 10.1080/1331677x.2020.1828130
|View full text |Cite
|
Sign up to set email alerts
|

How does CSR enhance the financial performance of SMEs? The mediating role of firm reputation

Abstract: This study investigates the link between corporate social responsibility (CSR) and the performance of small and medium enterprises (SMEs) and the mediating role of firm reputation from a developing country perspective. Empirical research was carried out, and data were gathered using a questionnaire from 402 owners/managers of SMEs in Eritrea, a country in East Africa. Smart-Partial Least Squares structural equation modelling was employed. The results showed that CSR significantly influences the performance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(115 citation statements)
references
References 119 publications
(108 reference statements)
4
98
0
13
Order By: Relevance
“…The findings also show that “firm reputation” positively and significantly impacts firm performance ( β = 0.425, p < 0.001). The result of this study is in line with the findings of Bahta et al (2020) in which firm reputation significantly affects SME performance. Corporate reputation enhances investors, customers and employees' satisfaction and plays a vital role in increasing profitability.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings also show that “firm reputation” positively and significantly impacts firm performance ( β = 0.425, p < 0.001). The result of this study is in line with the findings of Bahta et al (2020) in which firm reputation significantly affects SME performance. Corporate reputation enhances investors, customers and employees' satisfaction and plays a vital role in increasing profitability.…”
Section: Discussionsupporting
confidence: 91%
“…The results revealed that except for “indirect support to the community,” the three determinants are positively and significantly correlated with enterprise reputation and firm performance. Additionally, these results also have been confirmed by previously published studies including Khan and Yu (2020), Khan and Dong (2017), Khan et al (2019), Bahta et al (2020), Hertel and Wiesent (2013), Dues et al (2013), Saha et al (2020).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The finding of this study is also congruent with several studies (Iguchi et al, 2021;Mazereeuw et al, 2014;Tahir et al, 2015) who revealed that managers perceived religiosity and CSR practices are an important part of business. Some studies have demonstrated that CSR practice lead to a firm's corporate reputation (Bahta et al, 2021;Chef et al, 2021;Diogo & Neil, 2017;Gagalyuk, 2017). The finding suggests that the responding firms realise the benefits of CSR practice in enhancing their corporate image.…”
Section: Resultsmentioning
confidence: 99%
“…Corporate reputation could be referred as a reflection of the degree to which the public is satisfied that firms are meeting their expectations with products and services (Brammer & Pavelin, 2016) and enhance the firm's performance (Bahta et al, 2021;Chef et al, 2021;Pallathadka & Pallathadka, 2020). New and emerging issues in the market have called upon firms to focus on building their reputation in order to enhance their credibility and image.…”
Section: Literature Review Corporate Reputationmentioning
confidence: 99%